Genetic and genomic nursing competency among nurses in tertiary general hospitals and cancer hospitals in mainland China: a nationwide survey - Kathleen Calzone; Yi Liu; Juan Xu; Xueling Xiao; Honghong Wang; Xuying LI; Xiaomin Zhao (BMJ Open)
Objectives To explore genetic/genomic nursing competency and associated factors among nurses from tertiary general and specialist cancer hospitals in mainland China and compare the competencies of nurses from the two types of hospitals.Design and setting A cross-sectional survey was conducted from November 2019 to January 2020, wherein 2118 nurses were recruited from 8 tertiary general hospitals and 4 cancer hospitals in mainland China. We distributed electronic questionnaires to collect data on nurses’ demographics, work-related variables and genomic nursing competency.Participants 2118 nurses were recruited via a three-stage stratified cluster sampling method.Results More than half (59.1%, 1252/2118) of the participants reported that their curriculum included genetics/genomics content. The mean nurses’ genomic knowledge score was 8.30/12 (95% CI=8.21 to 8.39). Only 5.4% had always collected a complete family history in the past 3 months. Compared with general hospital nurses, slightly more cancer hospital nurses (75.6% vs 70.6%, p=0.010) recognised the importance of genomics, while there was no significant difference in the knowledge scores (8.38 vs 8.21, p>0.05). Gender (β=0.06, p=0.005), years of clinical nursing (β=−0.07, p=0.002), initial level of nursing education (β=0.10, p<0.001), membership of the Chinese Nursing Association (β=0.06, p=0.004), whether their curriculum included genetics/genomics content (β=0.08, p=0.001) and attitude towards becoming more educated in genetics/genomics (β=0.25, p<0.001) were significantly associated with the nurses’ genomic knowledge score.Conclusion The levels of genomic knowledge among mainland Chinese nurses in tertiary hospitals were moderate. The overall genomic competency of cancer hospital nurses was comparable to that of general hospital nurses. Further genomic training is needed for nurses in China to increase their genomic competency and accelerate the integration of genomics into nursing practice.